MATERNAL OUTCOMES OF PREGNANCY-RELATED ACUTE KIDNEY INJURY - Khattak, Muhammad Irfan; khattak, Samina Naseem; Imran, Ayesha; Kamal, Khawar; Yaqoob, Umairah (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of Pregnancy-related acute kidney injury in the Pakistani population and its effect on maternal health.Study Design: Cross-sectional study.Place and Duration of the Study: Department of Nephrology and Obstetrics and Gynecology, Combined Military Hospital Kharian, from Jan 2018 to Dec 2020.Methodology: All pregnant women with normal renal functions at the time of enrolment in the study and no previous history of any kidney disease or renal procedure in the recent past (at least 3 months) before conception were included in our study at Combined Military Hospital Kharian. All participants had serum creatinine tested at enrolment and were inquired specifically about any history of renal disease or any renal procedure in the recent past (at least 3 months old).Results: Mean maternal age in the study was 29 ± 7.67 years however it ranged from 16-41 years. Around a quarter of acute kidney injury cases occurred in the first and second trimesters combined, with 26 (12%) and 24 (11%) cases in the first and second trimesters, respectively. Thirty percent of acute kidney injury cases were diagnosed in the third trimester. A substantial number 58 (27%) of cases developed azotemia which persisted beyond three months and developed chronic kidney disease of various stages. Regarding maternal outcomes, 166 (77%) mothers recovered completely. However, 43 (20%) patients had some degree pf azotemia, a few cases required permanent renal replacement therapy.Conclusion: Acute kidney injury is a common problem in our community leading to suboptimal maternal outcomes..............